The Cultural Significance Of Traditional Wooden Furniture: A Case Study Of ‘Takhtah’, Sana’a Yemen - Mohammed Ali Abdo, Fatema (2019)
This study discusses one ignored issue on movable heritage furniture properties and its cultural significance. ‘Takhtah’ is a traditional wooden coffee table and a cabinet. It was often used in the traditional houses of the Old City of Sana'a. “Takhtah* can no longer be seen in many traditional houses as it was replaced by more contemporary furniture. This study aims to highlight the cultural significance of the Takhtah as a movable furniture element in Sana'a Heritage House. This study is a qualitative study as it investigates Takhtah as a case study.